An Analysis of Technological Innovation Management (International Journal of Innovative Research in Engineering & Management, 2021)
In high-tech & inventive companies, innovation & technology  management is an unavoidable problem. Organizations must  always concentrate on new product creation in order to  maintain market leadership. Innovations play a critical part in  product development in any company in order to expand business quicker, improve efficiency, & assist any  organization dominate in global market. In present scenario,  every company is attempting to integrate technology in  workplace in order to provide a better route to innovation that  will enable them to outperform ir rivals. Any organization's  business is immediately affected by technological innovation,  which is why good management of innovation & technology  is critical inside company. Effective management may assist  any company in maintaining its market leadership position.  This article offers an overview of business innovation,  concentrating on various kinds of innovation depending upon several criteria, technological innovation in digital business  environment, obstacles, & technological innovation  management.
Keywords: Innovation; Proactive; Product; Process; Reactive